Managing stormwater for urban sustainability: an evaluation of local comprehensive plans in the Chesapeake Bay watershed region. Issue 10 (3rd October 2017) - Kim, Hyun Woo; Li, Ming-Han
Abstract : This study uses a developed plan coding protocol in evaluating the quality of 76 comprehensive plans to examine whether local comprehensive plans have adequately integrated the concepts of sustainable stormwater management. The Chesapeake Bay watershed was chosen for the investigation because degraded stormwater runoff from nearby urban and suburban jurisdictions have critically polluted the watershed. The findings indicate that the majority of local governments have not sufficiently incorporated the sustainable stormwater management principles into their comprehensive plans. Five plan components (factual basis, goals and objectives, inter-organizational cooperation, policies, tools and strategies, and implementation) appear weak in realizing the concepts. The current study concludes by providing policy implications and recommendations to increase awareness and understanding of sustainable stormwater management concepts and to produce better implementation plans that integrate stormwater, ecosystem, and environmental planning comprehensively.